Increasing Trends in Mental Health Problems Among Urban Chinese Adolescents: Results From Repeated Cross-Sectional Data in Changsha 2016–2020 - Wu, Zhipeng; Wang, Biao; Xiang, Zhibiao; Zou, Zhulin; Liu, Zhening; Long, Yicheng; Chen, Xudong (Frontiers in Public Health, 2022)
This study performed a repeated cross-sectional analysis to explore possible trends in mental health problems among Chinese adolescents over the years of 2016–2020. A total of 2,837 different seventh-grade students were surveyed in three waves from a junior high school in Changsha city, Hunan province in China (978 in 2016, 949 in 2019, and 910 in 2020) using the Mental Health Inventory of Middle School Students (MMHI-60). The results showed that obsessive-compulsive tendencies, interpersonal sensitivity, depression, anxiety, academic stress, and emotional disturbance problems were significantly increased in surveyed adolescents from 2016 to 2020. Moreover, positive rates of most of these problems were significantly higher in females than males, and were significantly increased in only females. These results highlight the importance of focusing on mental health problems among urban Chinese adolescents, especially among girls.